2021
DOI: 10.3389/fnhum.2021.617626
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Prefrontal Cortex Hemodynamic Responses to the Fist-Edge-Palm Task in Naïve Subjects Using Functional Near-Infrared Spectroscopy

Abstract: The Fist-Edge-Palm (FEP) task, a manual hand task, has been used to detect frontal dysfunctions in clinical situations: its performance failures are observed in various prefrontal cortex (PFC)-related disorders, including schizophrenia. However, previous imaging studies reported that the performance of the FEP task activated motor-related areas, but not the PFC. Here, we aimed to investigate the relationships between the performance of the FEP task and PFC functions. Hemodynamic activity in the PFC, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…There was also a positive association between all three SPQ factor scores, odd speech and social anxiety scores with the average activation of the four right channels, whereas the unusual perceptual experiences subscale score was positively associated with average activation of the four right and left prefrontal (BA 10, BA 46 areas) channels [ 51 ]. Kobayashi et al [ 52 ] did not find significant effects of schizotypal traits on PFC activation patterns during a fist-edge-palm (FEP) test.…”
Section: Resultsmentioning
confidence: 99%
“…There was also a positive association between all three SPQ factor scores, odd speech and social anxiety scores with the average activation of the four right channels, whereas the unusual perceptual experiences subscale score was positively associated with average activation of the four right and left prefrontal (BA 10, BA 46 areas) channels [ 51 ]. Kobayashi et al [ 52 ] did not find significant effects of schizotypal traits on PFC activation patterns during a fist-edge-palm (FEP) test.…”
Section: Resultsmentioning
confidence: 99%
“…Previous fNIRS research demonstrated that adaptation to robot-assisted motor tasks promotes the user's active engagement, which leads to greater variability associated with sensorimotor cortex activation (Berger et al, 2019 ). Based on recent fNIRS evidence on learning novel skillful movements, such a brain-behavior association may be governed by top-down modulation from the rmPFC (Ota et al, 2020 ; Kobayashi et al, 2021 ). Furthermore, previous neuroimaging research revealed that providing robotic assistance for voluntary limb movement may involve the fronto-centro-parietal network (García-Cossio et al, 2015 ; Youssofzadeh et al, 2016 ; Memar and Esfahani, 2018 ), which has been regarded as the top-down executive control network, of which the rmPFC area is a higher-order component (Peng et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the rmPFC in top-down executive control in the performance of novel motor tasks has been investigated in a variety of study contexts. For example, several functional near-infrared spectroscopy (fNIRS) studies have reported that the involvement of high-level cognitive activities of PFC areas, including the rmPFC, is involved in learning novel upper limb motor skills (Ishikuro et al, 2014 ; Kobayashi et al, 2021 ). Recent work on fNIRS-based neurofeedback training also found that the anterior PFC, which corresponds to the rmPFC in this study, plays a role in top-down modulation of activity in the sensorimotor cortex in order to optimize motor performance (Ota et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A head cap with receptacles for NIRS probes was set on the head of participants, and its position was adjusted such that the lowest and most anterior NIRS probes were located on the FP2-FP10 line in the electroencephalogram 10–20 system ( Jurcak et al, 2007 ). A total of 28 optical sources and 32 detector probes were attached to the head cap ( Figure 1 ; Hibi et al, 2020 ; Kobayashi et al, 2021 ). Twenty-seven and five detector probes were placed at 3.0 and 1.5 cm from the source probes, respectively ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…Hemodynamic signals from the detector-source pairs with inter-probe distances less than 1.5 cm mainly reflect hemodynamic changes in the structures outside the brain (non-cerebral channels). To remove hemodynamic signals from structures outside the brain, a probe arrangement with multiple inter-probe distances was used, as previously described ( Saager et al, 2011 ; Ishikuro et al, 2014 ; Sato et al, 2016 ; Nakamichi et al, 2018 ; Hibi et al, 2020 ; Kobayashi et al, 2021 ). Signals from 95 composite and five non-cerebral channels were recorded ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%